Analysis Of The Application Of The Independent Curriculum In History Subjects At Muhammadiyah 2 Genteng High School - Aulita Inestya Putri; I Kadek Yudiana; Riztika Widyasari (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
One of the high schools that implement the independent curriculum is SMA Muhammadiyah 2 Genteng with a fairly good cultivation of religious character. This study aims to determine the journey of implementing the Merdeka Curriculum in History subjects at Muhammadiyah 2 Genteng High School. This research uses a constructivistic approach, education, history learning. This research also uses a qualitative method with the stages of determining the location and time of research, determining the form and strategy of research, determining data sources, determining data collection techniques, data validation techniques, and data analysis techniques. The data collection technique used was purposive sampling technique by means of observation, interviews and documentation. The interview subjects were the principal, curriculum deputy, history teacher, grade X and XI students. The results of the study explain that the implementation of the independent curriculum has been implemented for 2 years. In its implementation, there are three processes carried out, namely planning, implementation and evaluation. However, in its implementation there are several challenges that must be faced, one of which is the teacher's understanding of the new curriculum. Even so, the school is able to implement the independent curriculum well. This can be seen from the cultivation of religious character and student talent which continues to progress and the efforts made by the school. One of the efforts made is training, ongoing collaboration between teachers and continuous evaluation that can improve the implementation of the independent curriculum so as to improve the quality of education for the better.